Progreso genetico en trigo cultivado en secano - Ortega, D.=700 1 Manera, G.; Astolfi, G.; Argenti, R.; Maich, R.
(Es, En)
ilus., 10 ref.
Keywords: TRIGO; MEJORA GENETICA; RENDIMIENTO; CULTIVOS DE SECANO; ARGENTINA